Enhanced mechanical, thermal and adhesion properties of addition cured polydimethylsiloxane nanocomposite adhesives. (September 2022) - Anoop, V.; Sankaraiah, Subramani; Chakraborty, Sohini; Mary, N.L.
Abstract: The reinforcement of elastomeric polydimethylsiloxanes (PDMS) with carbon-based fillers and silica has gained much attention over the last few decades due to the inherent stability of the fillers which improves the physical and mechanical properties of the polymer nanocomposites. We report herein the preparation of an addition cured V-PDMS (vinyl-terminated PDMS) nanocomposite using CNT (carbon nanotube) and Aerosil COK 84 (mixed silica and alumina) as fillers. The influence of the fillers on the morphology, mechanical properties, thermal stability, thermal conductivity, and adhesive strength of these addition cured PDMS nanocomposites was studied in detail. It was observed that the tensile strength and thermal stability of the nanocomposites were enhanced upon the addition of fillers. The higher thermal conductivity of the CNT reinforced nanocomposites has potential application in heat sealing materials. The adhesive strength was studied by conducting a lap shear test on both mild steel and aluminum substrates and the adhesive strength was found to be higher for the mild steel substrate.